In vivo NMR studies of the metabolic response of plant tissues to anoxia - Ratcliffe, R (1997)
In vivo nuclear magnetic resonance (NMR) spectroscopy is a non-invasive technique that can be used to investigate the metabolic response of plant tissues to anoxia. It has been used extensively in studies aimed at assessing the contribution of particular pathways to energy production and pH control during oxygen deprivation; and it is also a powerful method for investigating the origin and metabolic significance of the intracellular pH changes that occur in anoxic tissues. Recent N MR investigations of plant anaerobiosis are reviewed and it is concluded: (a) that the NMR approach provides a detailed description of the time-dependent interaction between some of the key pathways of carbon and nitrogen metabolism under anoxia; and (b) that it can provide strong evidence for the direct effect of pH on metabolism, and for the biochemical pH-stat model of the anoxic response. The significance of the NMR contribution to the understanding of plant anaerobiosis is discussed, and the possibility that the well characterized role of pH in anaerobic metabolism could mask a more fundamental role for Ca2+ is considered. Finally, the future prospects lot NMR in this field are outlined and it is concluded that the continuing development of the technique itself, coupled with the increasing availability of transgenic plants, will extend the opportunities for testing metabolic hypotheses in vivo, and should therefore guarantee further significant contributions to the understanding of plant anaerobiosis.